Type and Duration of Exercise in the SAMMPRIS Trial. Issue 1 (January 2019) - Turan, Tanya N.; Al Kasab, Sami; Nizam, Azhar; Hannah, Jessica; Gordon, Neil; Lynn, Michael J.; Derdeyn, Colin P.; Fiorella, David; Janis, L. Scott; Lane, Bethany F.; Montgomery, Jean; Chimowitz, Marc I.
Abstract : Background: Analyses from the Stenting and Aggressive Medical management for prevention of Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) trial showed that good control of vascular risk factors (systolic blood pressure, low-density lipoprotein, and exercise) was associated with fewer vascular events and exercise had the biggest impact on the outcome. We sought to determine the type and duration of exercise performed by SAMMPRIS patients during the trial. Methods: SAMMPRIS aggressive medical management included a telephonic lifestyle modification program, INTERVENT, that was provided free of charge to all subjects during the study. We analyzed self-reported data collected by INTERVENT on the patients' type and duration of exercise from baseline (n=394) to 3 years (n=132). We calculated the mean duration for each exercise type at each time period and then compared the change in exercise duration from baseline using paired t tests and Wilcoxon signed-rank tests. Results: Walking was the most common form of exercise at all time points, as measured by both the duration of exercise and the number of patients performing the exercise. The mean duration of walking and other aerobic activities increased significantly from baseline to all other time points. Conclusions: The type of self-reported exercise performed by SAMMPRIS patients included mostly walking or other aerobic activity and increased significantly during follow-up.